Missing microbes : how the overuse of antibiotics is fueling our modern plagues - Blaser, Martin J. (New York : Henry Holt and Company, 2014)
"A critically important and startling look at the harmful effects of overusing antibiotics, from the field's leading expert Tracing one scientist's journey toward understanding the crucial importance of the microbiome, this revolutionary book will take readers to the forefront of trail-blazing research while revealing the damage that overuse of antibiotics is doing to our health: contributing to the rise of obesity, asthma, diabetes, and certain forms of cancer. In Missing Microbes, Dr. Martin Blaser invites us into the wilds of the human microbiome where for hundreds of thousands of years bacterial and human cells have existed in a peaceful symbiosis that is responsible for the health and equilibrium of our body. Now, this invisible eden is being irrevocably damaged by some of our most revered medical advances--antibiotics--threatening the extinction of our irreplaceable microbes with terrible health consequences. Taking us into both the lab and deep into the fields where these troubling effects can be witnessed firsthand, Blaser not only provides cutting edge evidence for the adverse effects of antibiotics, he tells us what we can do to avoid even more catastrophic health problems in the future. "--
"Tracing one scientist's journey toward understanding the crucial importance of the microbiome, this revolutionary book will take readers to the forefront of trail-blazing research while revealing the damage that overuse of antibiotics is doing to our health: contributing to the rise of obesity, asthma, diabetes, and certain forms of cancer. In Missing Microbes, Dr. Martin Blaser invites us into the wilds of the human microbiome where for hundreds of thousands of years bacterial and human cells have existed in a peaceful symbiosis that is responsible for the health and equilibrium of our body. Now, this invisible eden is being irrevocably damaged by some of our most revered medical advances--antibiotics--threatening the extinction of our irreplaceable microbes with terrible health consequences. Taking us into both the lab and deep into the fields where these troubling effects can be witnessed firsthand, Blaser not only provides cutting edge evidence for the adverse effects of antibiotics, he tells us what we can do to avoid even more catastrophic health problems in the future"--
Modern plagues -- Our microbial planet -- The human microbiome -- The rise of pathogens -- The wonder drugs -- The overuse of antibiotics -- The modern farmer -- Mother and child -- A forgotten world -- Heartburn -- Trouble breathing -- Taller -- And fatter -- Modern plagues revisited -- Antibiotic winter -- Solutions.
Includes bibliographical references (pages 221-256) and index.
Keywords: Antibiotics; Antibiotics -- Effectiveness; Drug resistance in microorganisms; SCIENCE / Life Sciences / Human Anatomy & Physiology; SCIENCE / Life Sciences / Biology / General; HEALTH & FITNESS / Diseases / Immune System; Antibiotics; Antibiotics -- Effectiveness; Drug resistance in microorganisms